Performance of Flood Tolerant Rice Variety (Swarna Sub-1) in Different Submergence Areas of Bihar - Singh, Ashok K.; Singh, J. P. (Indian Journal of Extension Education, 2013)
On one hand, continued depletion of natural resources, persistent technological stagnation and climate change are posing  serious threat to agriculture, while on the other side, vast potential area of submergence and flood-prone, are lying under  exploited. The recent strategy for reducing poverty and hunger through enhancing food security and improving  livelihood of farm families lies on the development and dissemination of high yielding varieties that are flood tolerant. In  this regard, International Rice Research Institute (IRRI) with collaboration of NARES partners has made considerable  progress to develop certain rice varieties, which are found flood resistant. Out of which SWARNA SUB-1 is most  promising rice variety, which has shown excellent results on farmer's field under flash flood condition of eastern India.  The present paper examines the importance of the situation in details with reference to Bihar state and highlighted the  performance of this variety along with the farmer's perception in different submergence areas of the State. Based on  experience and lesson learnt, there is an urgent need to develop appropriate farmer's centered seed production and delivery  mechanism strategy for rapid and targeted dissemination of this variety among the resource poor farmers who are residing  in flood- prone, condition of South Asia.
Keywords: Rice; cultivars; cooperation